Sammlung / Zentrum Paul Klee Bern - Zentrum Paul Klee (2006)
[Dt.:] Das Zentrum Paul Klee verfügt mit gut 4000 Werken über die weltweit bedeutendste Sammlung von Gemälden, Aquarellen und Zeichnungen Paul Klees (1879-1940) und zusätzlich über zahlreiche biografische Text- und Bilddokumente. Rund 150 Exponate sind über eine Datenbank recherchierbar und mit Katalogisaten versehen. - [Engl.:] With around 4000 works the Zentrum Paul Klee boasts the worlds most important collection of paintings, watercolours and drawings by Paul Klee (1879-1940) as well as a great deal of biographical material in text and picture form. Besides general information the website offers a database: The images are described in detail, the thumbnails can be zoomed.